Self-heating ignition of large ensembles of Lithium-ion batteries during storage with different states of charge and cathodes. (October 2021) - He, Xuanze; Hu, Zhenwen; Restuccia, Francesco; Yuan, Han; Rein, Guillermo
Highlights: Cell thermal runaway temperature of standard SAE-J2464 is insensitive to size. The critical ambient temperature triggering ignition decreases with size. The critical ambient temperature should be used for safe storage, rather than using the critical temperature increase rate. Model predicts cells with higher SOC or Lithium Cobalt Oxide cathode are easier to self-ignite. Abstract: Self-heating is a possible cause of ignition of the open-circuit Lithium-ion battery (LIB) during storage. However, previous studies mainly focused on self-heating of a single cell, without considering the effect of heat transfer on large-size storage. In this study, a one-dimensional computational model, coded in the Gpyro, is used to study ensembles containing 1 cell to 5 million cells. Results show that ignition occurs at the central cell of the ensemble, while the outer surfaces remain at ambient temperature. As the length of ensembles increases from 0.01 m to 10 m, cell thermal runaway temperatures quantified using the critical temperature increase rate of 10 °C/min as defined in standard SAE-J2464 are insensitive to ensemble size, decreasing from 188 °C to 184 °C, but the critical ambient temperature triggering ignition decreases with size from 183 °C to 98 °C. This shows that the critical ambient temperature should be used to guide storage rather than the standard suggested critical temperature increase rate, which does not represent the criticality of ignition. The model predicts that higher state of charge (SOC) cells are easier to self-ignite. An ensemble containing 5 million 80% SOC cells can self-ignite at 40 °C. Self-heating ignition propensity of the Lithium Cobalt Oxide cathode LIB is larger, compared with Lithium Nickel Cobalt Manganese Oxide cathode. This study finds that the SAE-J2464 standard is not sufficiently robust to understand self-heating ignition during storage, and predicts the effect of the SOC and cathode chemistry on critical ambient temperature, contributing to the protection against LIB fires.